Aksjomaty prawomocnego dyskursu, czyli co jest wykluczone w debacie nad wykluczeniem społecznym - Lipski, Aleksander (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: Axioms legitimate discourse, or what is excluded in the debate on social exclusion The debate on social exclusion takes place within the discourse-based system of axioms relevant to market society. Discourse is treated naturally and does not require substantiation. As a result, eliminated from the debate are the questions that undermine its legitimacy. The current discourse illustrates the daily practice of living a “normal” majority. Cultural obligations are excluded (that was not a minority) is to undergo rehabilitation under the terms of a legitimate social system. Key words: legitimate discourse, social exclusion, market society, resocialisation